Peter (Panayotis) Karavites: Capitulations and Greek Interstate Relations. The Reflection of Humanistic Ideals in Political Events. Hypomnemata, Heft 71 Vandenhoeck & Ruprecht, Göttingen 1982, 142 S. - Chaniotis, Angelos (Gerión. Revista de Historia Antigua, 1983)
Sin resumen